The Effect Of Deferred Tax Expense On Earnings Management: (Empirical Study on PT. Matahari Department Store, Tbk Listed on The Indonesia Stock Exchange in 2015 to 2019) - Hasan Rachmany; Tajudin Tajudin (LPPM-STPI, 2022)
In PSAK No. 1 concerning the preparation of financial statements, the financial statements can then assess the size of the company's performance. As a basis for making business decisions, one of which is company profits. Therefore, company managers want to increase reported earnings for shareholders and external users of financial statements. This is called earnings management practice. This study aims to analyze the effect of deferred tax expense on earnings management, determine the amount of deferred tax expense and corporate earnings management. The data used in this study comes from audited financial statements at PT. Matahari Department Store, Tbk which are listed on the Indonesia Stock Exchange for the 2015-2019 period. This study uses a non-probability sampling technique, by means of saturated sampling. The data analysis used in this research is linear regression analysis, classical assumption test, t-test, f-test, and coefficient of determination. The results of this study indicate that deferred tax expense has no significant effect on earnings management with a coefficient of determination of 34.4%. Deferred tax expense cannot detect any earnings management at PT. Matahari Dept. Store,Tbk. As well as the magnitude of negative earnings management because the net profit per year is greater than cash inflows from operational activities.